Evaluación de la calidad de la materia prima para la elaboración de concentrado de piña (Agroindustria, Sociedad y Ambiente, 2018)
The fruits destined to the elaboration of concentrates require to fulfill with the minimum specifications to obtain a product of quality. The objective of the work was to evaluate the quality of the raw material destined to the elaboration of pineapple concentrate (Ananas comosus L. Merr). The study was carried out in a pineapple processing company, the physical quality of the fruits was evaluated, determining the variables fresh mass (MF), equatorial diameter (DE), polar diameter (DP), maturity index (MI), index of Fruit deformity (IDF), epidermis color scale (ECE), gummosis presence index (IPG), presence of damage (PD) and in chemical quality, the total soluble total solids (TSS) expressed in ( °Brix), pH, and total titratable acidity (ATT), by the methods described by the Venezuelan Commission of Industrial Standards (COVENIN). A completely randomized design with 3 replications was used, the data were analyzed in the statistical program Statistix 8. The results of the physical evaluation of the fruits indicate variability in fresh mass with values between 400 and 600 g, immature fruit (20.5 %) on maturation (38.7%), incidence of gummosis (32.2%) and fruit malformation (14.4%). Regarding the chemical variables, significant differences were found with values close to the reference values of SST between 10.0 and 13.0 ° Brix, pH between 3.2 and 3.5 and ATT between 0.40 and 0.60 (% citric acid). The raw material received in the company presented differences in size, diameter below those required, rate of immature maturity or overgrowth, deformed pineapples, incidence of gummosis and physical damage
Keywords: Ananas comosus L. Merr; physical characteristics; chemical characteristics; post-harvest